2013
DOI: 10.1524/zpch.2013.0414
|View full text |Cite
|
Sign up to set email alerts
|

Models for Intrinsic Non-RRKM Dynamics. Decomposition of the SN2 Intermediate Cl––CH3Br

Abstract: Chemical dynamics simulations, based on both an analytic potential energy surface (PES) and direct dynamics, were used to investigate the intrinsic non-RRKM dynamics of the Cl products were fit with multi-exponential functions. The intrinsic non-RRKM dynamics is more pronounced for the simulations with the analytic PES than by direct dynamics, with the populations for the former and latter primarily represented by tri-and bi-exponential functions, respectively. For the analytic PES and direct dynamics simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The intrinsic non-RRKM dynamics of the Cl − ---CH 3 Br S N 2 intermediate were studied by trajectories on an analytic potential energy surface and by direct dynamics. 31 Different models were used to represent the phase space dynamics and nonexponential P(t), including a multiexponential function.…”
Section: Unimolecular Rate Constants Without the Steady-state Approxi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The intrinsic non-RRKM dynamics of the Cl − ---CH 3 Br S N 2 intermediate were studied by trajectories on an analytic potential energy surface and by direct dynamics. 31 Different models were used to represent the phase space dynamics and nonexponential P(t), including a multiexponential function.…”
Section: Unimolecular Rate Constants Without the Steady-state Approxi...mentioning
confidence: 99%
“…Effects of intrinsic non-RRKM dynamics on k uni (ω, E ) and k (ω, E ) have been investigated in previous studies. ,, Multiexponential P ( t ) have been used to calculate k (ω, E ) in eq for model HCC → H + CC dissociation , to compare with chemical dynamics simulations and for Cl – ---CH 3 Cl → Cl – + CH 3 Cl dissociation to compare with chemical dynamics simulations and experiments. , Effects of fluctuations in quantum mechanical state-specific rate constants, and their distributions, on the unimolecular rate constants k uni (ω, E ) and k (ω, E ) have been considered. , An example is the relationship between quantum dynamical calculations of the highly mode-specific decomposition for HOCl → OH + Cl and the Lindemann–Hinshelwood unimolecular rate constant k uni (ω, T ) in eq . In interpreting experimental measurements of k uni (ω, T ) for HCO → H + CO dissociation, Hippler and co-workers found that a mode-specific isolated resonance model represented their experimental results.…”
Section: Unimolecular Rate Constants Without the Steady-state Approxi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is hardly surprising that several studies have identied reactions which are intrinsically non-RRKM in nature. [7][8][9][10][11][12][13][14] Such studies are leading to much needed insights into the dynamics, and hence aiding in identifying novel mechanisms and raising hopes for targeted control of the reaction. Clearly, it is crucial to develop models for reaction rates that eschew the statistical assumption and provide insights into the mechanisms for nonstatistical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…A similar behavior was observed at 300 kcal/mol energy also, f 1 = 0.47, k 1 = 2.09 ps –1 , f 2 = 0.53, k 2 = 0.59 ps –1 , i.e., a fast and a slow component were observed. To investigate the nonstatistical dynamics, various coupled phase space models have been proposed, but such studies were not performed any further in the present work.…”
Section: Discussionmentioning
confidence: 99%